Pelatihan Pemanfaatan Edmodo Sebagai Sarana Pembelajaran Daring Di Sekolah Dasar - Lucia Sri Istiyowati; Agnes Novita; Elliana Gautama; Nani Tachjar; Pratiwi (Ikatan Ahli Informatika Indonesia, 2021)
Pamardi Yuwana Bhakti (PYB) is a school owned by the Foundation and has schools ranging from playgroups to junior high schools. This school was founded in 1983 and has approximately 50 teachers, classes and by 2020 the Pamardi school will graduate more than 1000 students. Learning that is introduced to students, like learning in general, is conventional in the sense of being face-to-face. The Covid-19 pandemic that has hit the whole world has an impact on all human life, as well as the world of education. The pandemic caused by the coronavirus has hampered learning activities in schools which usually take place face-to-face. The pandemic that is also felt by the teachers at PYB schools requires them to quickly adapt and learn to use technology in managing learning activities, learning tools like Quizizz or Kahoot, etc. Currently, it is done in a conventional way, it has to change due to the impact of COVID-19 because learning activities must be carried out remotely since March 2020. Activities are carried out by means of workshops using school laboratories and teacher laptops so that teachers can immediately try and use the application